Effect of Date of Planting and Spacing on Growth and Yield of Sprouting Broccoli (B. oleraceae (L.) var. italica Plenck) cv. Green Magic - Saha, Tanmoy; Basfore, Shibnath; Choudhury, Riman Saha; Sikder, Subhamoy; Debnath, Manoj Kanti (International Journal of Bio-resource and Stress Management, 2023)
The field experiment was conducted during autumn-winter (October to December) seasons of 2017–18 and 2018–19 at Horticultural Farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India. Treatments comprised of four planting dates viz., D1: 21st October, D2: 28th October, D3: 7th November, D4: 14th November and four spacing viz., S1: 30×45 cm2, S2: 45×45 cm2, S3: 60×45 cm2 and S4: 60×60 cm2 were assessed in factorial randomized block design with three replications. The broccoli transplanted on 21st October (D1) reported significantly maximum head weight (464.95 g) and projected yield (11.46 t ha-1) which was statistically at par with 2nd date of planting D2 i.e 28th October (423.91 g and 11.03 t ha-1 respectively) over the other dates of planting, while the wider spacing S4 i.e. 60×60 cm2 showed significantly maximum head weight (400.74 g) over other spacing’s and closer spacing S1 i.e 30×45 cm2 had recorded significantly highest yield (13.48 kg plot-1 and 14.98 t ha-1). Interaction between date of planting and spacing was significant in respect of head yield per hectare. Maximum projected head yield (17.19 t ha-1) was obtained in D1S1: 21st October and 30×45 cm2 combination. After adopting the planting dates from October 21st (D1) to October 28th (D2) and closer spacing of 30×45 cm2 (S1) was found more gainful in terms of yield and other growth parameters also.